Capacity building and co-creation with bean value chain actors on the establishment of a demand led seed systems in Eastern and Southern Africa - Rubyogo, Jean-Claude; Kalemera, Sylvia Monica; Aseete, Paul (2022)
The growing demand in domestic and export market for common beans requires high quality seed with better yields. The use of poor seed leads to sorting, costly and yield poor grain quality. High quality seed of new varieties delivers quality grain and higher yields for farmers, both traders and farmers command premium prices. To achieve this the seed production needs to start working from the grain demand.